Corpus Dionysiacum / 2 Pseudo-Dionysius Areopagita. De Coelesti Hierarchia, De Ecclesiastica Hierarchia, De Mystica Theologia, Epistulae : 2., überarbeitete Auflage / Günter Heil, Adolf M. Ritter - Dionysius, Areopagita; Heil, Günter; Ritter, Adolf Martin (Corpus Dionysiacum, 2012)
This work is the second part of a critical textual edition that is devoted to an extraordinarily rich collection of manuscripts with equally remarkable historical significance dating from late Christian antiquity. Günther Heil; Adolf Martin Ritter,Universität Heidelberg.